2021
DOI: 10.1111/jors.12558
|View full text |Cite
|
Sign up to set email alerts
|

Who partners up? Homogamy and income inequality in New Zealand cities

Abstract: This paper examines the impact of homogamy on the distribution of household income in New Zealand at the national level and across different sized cities. We focus on homogamy by age, education, hours worked, employment status, and migration status. We present a new index of homogamy that takes account of maximum potential homogamy. Our index is less sensitive to categories with small population shares than the commonly used concentration ratios. We compare the inequality impact of actual matching with that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Two factors contributed to this: first, the working-age population increased by 36% (i.e., there were more people of working age); and second, a higher percentage of persons of working age were employed (69% vs. 63% in 2002). Population increase and labour force utilisation were both influenced by several reasons (Alimi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Two factors contributed to this: first, the working-age population increased by 36% (i.e., there were more people of working age); and second, a higher percentage of persons of working age were employed (69% vs. 63% in 2002). Population increase and labour force utilisation were both influenced by several reasons (Alimi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [7] confirmed a positive relationship between aging and income inequality due to a decrease in the labor share of elderly workers. Alimi et al [8] examined New Zealand and noted that the effect of reducing aging inequality was not significant in metropolitan areas where the rate of aging is slower.…”
Section: Introductionmentioning
confidence: 99%